The Influence of Product Quality, Promotion, and Shopee Paylater on Purchase Decision - Wira Tamtama, Manikam Manggala; Basuki, Ananto (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to analyze the influence of product quality, promotion, and Shopee PayLater on consumer purchasing decisions in Malang City. The research employs a quantitative approach using the Partial Least Square (PLS) method to analyze data collected from 170 respondents, selected through purposive sampling. The respondents were Shopee PayLater users aged 17-35 years who had seen promotions at least three times and made purchases in the last three months. The results show that product quality has the most significant influence on purchasing decisions, with a correlation coefficient of 0.411, followed by promotion with a coefficient of 0.308, and Shopee PayLater with a coefficient of 0.234. Although all three variables have statistically significant impacts, Shopee PayLater serves as a supporting variable compared to product quality, which is the main driver of purchasing decisions. This study concludes that a combination of good product quality, effective promotion, and flexible payment through Shopee PayLater can enhance consumer purchasing decisions.